Production of Methyl ester from Coconut Oil using Heterogeneous K/Al2O3 under Microwave Irradiation - Andi Suryanto; Ummu Kalsum; Lailatul Qadariya; Mahfud Mahfud (Journal of Chemical Process Engineering, 2020)
Methyl esters derived from coconut oil are very interesting to study because they contain free fatty acids with a medium carbon chain structure (C12-C14), so most methyl esters (70%) can be bio-kerosene and the rest can be biodiesel. The process of preparing methyl ester by reaction of Trans-esterification triglyceride generally using a homogeneous KOH catalyst but this process requires a long catalyst separation process through washing and drying process. The use of heterogeneous catalysts in the production of methyl esters can remove the washing and drying processes, but trans-esterification reactions with heterogeneous catalysts require severe conditions (high pressure and high temperature), whereas at low temperatures and atmospheric conditions, the methyl ester yield is relatively low. Using microwave-irradiated trans-esterification reactions with heterogeneous catalysts, it is expected to be much faster and can obtained higher yields. Therefore, in this study we prepare a heterogeneous catalyst K/Al2O3 using solution KOH that impregnated in catalyst support Al2O3, and catalyst obtained are caracterized by XRD, BET dan SEM. Our objective was to compare the yield of methyl esters obtained through the trans-esterification process of coconut oil assisted by microwave using a heterogeneous K / Al2O3 catalyst with yield obtained using a homogeneous KOH catalyst. Experimental equipment consists of a batch reactor placed in a microwave oven equipped with a condenser, agitator and temperature controller. The batch process was carried out at atmospheric pressure with variation of K/Al2O3 catalyst concentration (0.5, 1.0, 1.5, 2.0, 2.5%) and microwave power (100, 264 and 400 W). In general, the process of producing methyl esters by heterogeneous catalysts will get three layers, wherein the first layer is the product of methyl ester, the second layer is glycerol and the third layer is the catalyst. The experimental results show that the methyl ester yield increases with increasing of microwave power, catalyst concentration and reaction time. The results obtained with K /Al2O3 catalysts are generally slightly lower than those obtained using a homogeneous KOH catalyst. However, the yield of methyl esters obtained by the K / Al2O3 heterogeneous catalyst process are relatively easy to separate rather than using a homogeneous KOH catalyst.